Penerapan Teknologi Alat Sega Raharja untuk Pengolahan Limbah Ikan Runcah Menjadi Pelet Ikan - Wicaksono, Alvian; Sagaf, Muhammad; Mubarok, Bagas Ramadhani; Haryanto, Christi Adi; Gunawan, Ari; Lestari, Sugiana Putri; Pamungkas, Bintang Fajar (LPMP Imperium, 2025)
Dedication activities were held on February 26, 2025, in Sembir, Kutawaru Village, Cilacap Regency, Central Java, aiming to socialize the use of Sega Raharja tools to the coastal communities of Segara Anakan, Kutawaru, Cilacap. This tool is designed to help the group of fishermen, Pepes Sega K-Cap, reduce fish waste to produce fish feed independently by utilizing environmentally friendly technology. Methods of implementing activities include socialization, demonstration of tool use, and direct implementation assistance to coastal communities. Indicators of the success of this activity are that coastal communities can understand the benefits and how to operate the Sega Raharja equipment, and demonstrate high enthusiasm in adopting the technology to support operational cost savings, increase productivity, and improve the quality of fish feed. Additionally, this activity contributes to increasing public awareness of the importance of maintaining the sustainability of marine ecosystems through the use of environmentally friendly technology. Thus, the socialization of Sega Raharja tools not only has an economic impact on fishermen but also supports environmental conservation in the Segara Anakan coastal area.